Loneliness psychoeducation in the community of frater in Maumere - Epifania M. Ladapasea; Sitti Anggraini; Paulus Lunga; Natesha Fabiola Leto; Claudia Kasmayati Sari Kasih (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Loneliness is an unpleasant experience that occurs when a person experiences social relations that are low in quality or quantity. This situation can happen to anyone, including the brothers in the Brothers Community in Maumere. The brothers as candidates for priests who are involved in community life also experience loneliness in community life. This is due to being away from family members, lack of communication with family members, and lack of socialization with the surrounding community. The Loneliness Psychoeducation given will be a new resolution to find something of value behind the loneliness they experience. The brothers who were involved in this psychoeducational loneliness activity became more understanding about loneliness and found positive coping. The methods used in this psychoeducation are loneliness socialization methods, problem trees and group counseling. The result of this psychoeducation is that the brothers understand the loneliness they feel, are more open with themselves, and find positive coping in community life.